EVALUATION OF THE EFFECTIVENESS ON DISTANCE LEARNING DURING THE COVID-19 PANDEMIC AT POLITEKNIK PELAYARAN MALAHAYATI - tri cahyadi; Agus Dina Mirianto; Zainullah Zuhri; Novita Vindri Harini (Jurnal Maritim Malahayati, 2023)
This aim of this study is to determine the effectiveness on distance learning during the Covid-19 Pandemic at Politeknik Pelayaran Malahayati. The type of research that will be used is descriptive research. The descriptive type in this study was to describe the effectiveness on distance learning during the Covid-19 Pandemic in the Politeknik Pelayaran Malahayati. Descriptive research is research conducted to determine the value of independent variables, either one or more (independent) variables without making comparisons, or connecting one variable to another. The Covid-19 pandemic has changed the education system in Indonesia into distance learning using online media. This is done in order to reduce and stop the chain of distribution. The use of information technology in distance learning during the Covid-19 pandemic at Politeknik Pelayaran Malahayati was considered effective by cadets/I in terms of 5 indicators, namely (1) cadet characteristics during long distance learning, (2) cadets' understanding of long distance learning material, (3) Learning tools used by lecturers in long distance learning, (4) Interaction in long distance learning, and (5) cadets' learning achievement. On the other hand, there are still learning weaknesses, namely internet network constraints, the physical usefulness of physical learning is lacking, and the type of task is monotonous. In theoretical courses, long distance learning is very understandable and effective, but practical courses that require direct skills are quite effective, there are still some difficulties for cadets. Educators have a very decisive role in the success of this online learning. Educators must create creative, innovative, and recreational learning methods that stimulate cadets to be willing to be actively involved in online learning and feel the meaning of distance learning.